eGY-Africa: Addressing the digital divide for science in Africa - (:unkn) unknown (My University, 2009)
Adoption of information and communication technologies and access to the Internet is expanding in Africa, but be- cause of the rapid growth elsewhere, a Digital Divide be- tween Africa and the rest of the world exists, and the gap is growing. In many sub-Saharan African countries, educa- tion and research sector su er some of the worst de cien- cies in access to the Internet, despite progress in develop- ment of NRENs {National Research and Education (cyber) Networks. By contrast, it is widely acknowledged in policy statements from the African Union, the UN, and others that strength in this very sector provides the key to meeting and sustaining Millennium Development Goals. Developed coun- tries with e ective cyber-capabilities proclaim the bene ts to rich and poor alike arising from the Information Revo- lution. This is but a dream for many scientists in African institutions. As the world of science becomes increasingly Internet-dependent, so they become increasingly isolated. eGY-Africa is a bottom-up initiative by African scientists and their collaborators to try to reduce this Digital Divide by a campaign of advocacy for better institutional facili- ties. Four approaches are being taken. The present status of Internet services, problems, and plans are being mapped via a combination of direct measurement of Internet per- formance (the PingER Project) and a questionnaire-based survey. Information is being gathered on policy statements and initiatives aimed at reducing the Digital Divide, which can be used for arguing the case for better Internet facil- ities. Groups of concerned scientists are being formed at the national, regional levels in Africa, building on existing networks as much as possible. Opinion in the international science community is being mobilized. Finally, and perhaps most important of all, eGY-Africa is seeking to engage with the many other programs, initiatives, and bodies that share the goal of reducing the Digital Divide either
Keywords: African Research